Tranexamic Acid in Total Knee and Hip Arthroplasty: Dosing Strategies and Routes of Administration – A Narrative Review - Kopciał, Szymon; Kornatowska, Karolina; Wiekiera, Mateusz; Wiekiera, Adrianna; Budzik, Paweł (Quality in Sport, 2026)
Introduction and purpose: Perioperative blood loss remains a significant concern in total knee and hip arthroplasty (TKA, THA), leading to decreased hemoglobin levels and an increased requirement for blood transfusions. Tranexamic acid (TXA), a potent antifibrinolytic agent, is widely utilized to mitigate perioperative bleeding. The objective of this review is to evaluate TXA dosing strategies and administration routes, with a particular focus on timing, multidose protocols, and their subsequent impact on blood loss and clinical outcomes. Description of the state of knowledge: TXA effectively reduces total blood loss, hidden blood loss, and hemoglobin decline in TKA and THA. A single preoperative dose limits early bleeding but fails to suppress postoperative hyperfibrinolysis. Extended and multidose regimens within the first 24 hours provide superior control of fibrinolytic activity. Intravenous, oral, and topical routes show comparable efficacy, while combined strategies may enhance hemostasis. Additionally, TXA exerts anti-inflammatory effects (lowering IL-6 and CRP), reducing pain and edema while improving early clinical outcomes. Conclusions: TXA effectively reduces total and hidden blood loss in TKA and THA without increasing thromboembolic risk. Maximum clinical benefits are achieved through individualized, extended multidose regimens that ensure sustained suppression of postoperative hyperfibrinolysis and inflammation (IL-6, CRP). Optimized TXA protocols significantly enhance early recovery by reducing postoperative pain and edema.